Neuromuscular Fitness Is Associated with Serve Speed in Young Female Tennis Players - Zlatan Bilić; Paola Martić; Petar Barbaros; Filip Sinković; Dario Novak (MDPI AG, 2024)
In tennis, the serve plays a key role in determining the success of a player. The speed of a serve is influenced by a multitude of interconnected skills and abilities. The objective of this study was to establish the correlation between the explosive strength of the throwing type, the grip strength and flexibility of the arms, and the shoulder girdle with the serve speed in young female tennis players. Additionally, the study aimed to develop a regression model that accurately predicts the serve speed by analyzing the interplay among these variables. The study was carried out on a group of 20 tennis players, who had an average age of 13.10 ± 0.74 years. Additionally, their height was recorded as 165.70 ± 4.90 cm, and their body mass was measured at 51.45 ± 5.84 kg. To assess the motor abilities of the upper extremities, four tests were used that aimed to measure the explosive strength of the throwing type; one test was for the strength of the hand and forearm muscles, and one test was for the flexibility of the arms and shoulder girdle. Of all the variables examined, the medicine ball throw shot put (MBTSP) (r = 0.75), overhead medicine ball throw (OMBT) (r = 0.70), and grip strength (GS) (r = 0.71) displayed a notable correlation with serve speed (p < 0.05). The results obtained from the multiple regression analysis indicate that the combination of selected predictors (MBTSP-medicine ball throw shot put, OMBT-overhead medicine ball throw and GS-grip strength) explained 75% of the variability in serve speed. Significantly, MBTSP surfaced as the predominant predictor, autonomously elucidating 51% of the variability in serve speed. The importance of improving the analyzed motor skills of young female tennis players to enhance their serve in terms of speed is emphasized by the findings of this research.